The limits of applying the objectives of Sharia in explaining Sharia rulings - .djedid, djoudi; hammad., .boudjemaa (Journal of Social Sciences and Humanities, 2023)
The one who examines the classifications of the fundamentalists, it becomes clear to him that the purposes of legitimacy revolve around the ends, goals and outcomes that were intended by the author of the wise law to achieve human happiness and his interest in the world and the hereafter. And its goals, and thus Imam al-Juwayni declares in the proof: “Whoever does not realize that the intentions fall into commands and prohibitions, then he has no insight into establishing the Sharia, which is the direction of the mujtahids. Whoever turns to it from any direction will always be right.” These papers show the areas of the purposes of Sharia for the diligent and its controls.